If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2y + -6) = -9(y + -8) Reorder the terms: 3(-6 + 2y) = -9(y + -8) (-6 * 3 + 2y * 3) = -9(y + -8) (-18 + 6y) = -9(y + -8) Reorder the terms: -18 + 6y = -9(-8 + y) -18 + 6y = (-8 * -9 + y * -9) -18 + 6y = (72 + -9y) Solving -18 + 6y = 72 + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. -18 + 6y + 9y = 72 + -9y + 9y Combine like terms: 6y + 9y = 15y -18 + 15y = 72 + -9y + 9y Combine like terms: -9y + 9y = 0 -18 + 15y = 72 + 0 -18 + 15y = 72 Add '18' to each side of the equation. -18 + 18 + 15y = 72 + 18 Combine like terms: -18 + 18 = 0 0 + 15y = 72 + 18 15y = 72 + 18 Combine like terms: 72 + 18 = 90 15y = 90 Divide each side by '15'. y = 6 Simplifying y = 6
| 13x+1y=25 | | [-2x+4]=4 | | -3[2t+1]=9 | | -10=-4v-v | | 8x+1=10-5x | | 3/4[8t-12]=6(t-1) | | 2x-5x=y | | a+bi+6(a-bi)=7 | | 27rst+27tsr= | | 3/4[8t-12]=6(1-1) | | 13+-7-10x=2 | | -5b=25 | | 12*90= | | 5+2(x-2)=18 | | v+3=-1 | | 9/4t^-1 | | (-4)(u+2)=((3)(2u+4))+4 | | 10=-4v-v | | [3z-2]+5=9 | | (f/2)-4=1 | | 112+2x=22-4x | | 2[4x+1]-5=1 | | -24=2x-x+6 | | p+9=0 | | 1/2[2x-1]-3=1 | | 9x^5/27x^2 | | 270/3[(4-3)3-(-9)]-53 | | 3(y-2)+2y+5=9y-4+3y+1 | | -132+(-7)=-139 | | k+5=-5 | | -7x-83=29-3x | | x-9y=-39 |